Well-being balance and lived experiences assessment: a valid, comprehensive measure of positive well-being - McDermott, Ashley F.; Brydges, Christopher R.; Norris, Troy W. (Frontiers in Psychology, 2024)
Introduction Widely used measures of self-reported subjective well-being and flourishing generally do not directly measure positive experiences that have been demonstrated to improve subjective well-being and flourishing, which could aid in developing personalized interventions to improve individuals’ well-being. The present study evaluated the validity of the Well-being Balance and Lived Experience (WBAL) Model and Assessment, a new model of well-being and corresponding assessment instrument that evaluates the self-reported frequency of positive experiences and positive feelings of well-being, balanced across activation and arousal levels. Methods A total of 496 evaluable subjects completed the WBAL Assessment, the PERMA+ Profiler (PERMA+) and the Well-Being Assessment Adult 24-item (WBA-24). A confirmatory factor model corresponding to the WBAL construct was created, and internal and external validity of the WBAL Assessment were interrogated. Results The confirmatory factor model showed good fit, indicating that each of the model factors are related but distinct and all items load significantly onto their factors. The WBAL Assessment demonstrated high internal consistency (Cronbach’s α = 0.95) and internal validity across well-being factors and Feelings (r = 0.96) and Experiences (r = 0.94) domains. The WBAL Assessment demonstrated strong convergent validity in comparison to PERMA+ (r = 0.80) and WBA-24 (r = 0.75), indicating that the WBAL Assessment measures a similar overall concept of well-being and flourishing. Discriminant validity of WBAL factors was demonstrated for an average of 14.3 of 17 comparator domains. The main differences between instruments are WBAL’s assessment of positive Experiences, the comparator instruments’ inclusion of feelings with negative valence, and WBA-24’s inclusion of financial stability. Discussion The WBAL Assessment is a reliable and valid instrument to comprehensively measure positive aspects of well-being that evaluates multiple modifiable contributors to individuals’ well-being to guide design of personalized assessment and intervention programs to enhance positive well-being.